Cloud Analytics with Microsoft Azure : Build modern data warehouses with the combined power of analytics and Azure /: Build modern data warehouses with the combined power of analytics and Azure. (2019) - Altaiar, Has; Lee, Jack; Peña, Michael
No abstract available